2010
DOI: 10.1073/pnas.0909917107
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Tdp1 regulates the fidelity of nonhomologous end joining

Abstract: Tyrosyl-DNA-phosphodiesterase 1 (Tdp1) can disjoin peptides covalently bound to DNA. We assessed the role of Tdp1 in nonhomologous end joining (NHEJ) and found that linear DNA molecules with 5′ extensions showed a high frequency of misrepair in Δtdp1 cells. The joining errors in Δtdp1 cells were predominantly 2-4 nucleotide insertions. Ends with 3′ extensions or blunt ends did not show enhanced frequencies of errors, although Δtdp1 cells repaired blunt DNA ends with greater efficiency than WT cells. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 34 publications
5
69
1
Order By: Relevance
“…The tandem, 4-bp duplications seen here are of particular interest as they are similar to those recently reported using a plasmid-based NHEJ assay (Bahmed et al 2010(Bahmed et al , 2011. Because such duplications were observed only following transformation of linear molecules with cohesive 59 overhangs, it was proposed that they are generated by the precise ligation of filled-in, blunt ends ( Figure 5A).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…The tandem, 4-bp duplications seen here are of particular interest as they are similar to those recently reported using a plasmid-based NHEJ assay (Bahmed et al 2010(Bahmed et al , 2011. Because such duplications were observed only following transformation of linear molecules with cohesive 59 overhangs, it was proposed that they are generated by the precise ligation of filled-in, blunt ends ( Figure 5A).…”
Section: Discussionsupporting
confidence: 58%
“…Because such duplications were observed only following transformation of linear molecules with cohesive 59 overhangs, it was proposed that they are generated by the precise ligation of filled-in, blunt ends ( Figure 5A). In the plasmid-based assay, tandem duplications were elevated upon loss of either Tdp1 (Bahmed et al 2010) or Exo1 (Bahmed et al 2011). It was suggested that the 39-nucleosidase activity of Tdp1 converts the recessed 39-OH to a recessed 39-phosphate, thereby preventing the filling in of the enzyme-generated end (Bahmed et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An interesting model developed in yeast proposes that Tdp1 removes intact bases from otherwise undamaged 5 0 -overhanging DSBs such that the new 3 0 -phosphate lesion prevents undesirable filling of the overhang and insertional mutagenesis (Fig. 4E) (Bahmed et al 2010). …”
Section: Nucleases and Related Activitiesmentioning
confidence: 99%